Light noble gas data in Guli massif carbonatites reveal the subcontinental lithospheric mantle as primary fluid source - Buikin, Alexei I.; Kogarko, Lija Nikolaevna; Hopp, Jens; Trieloff, Mario (Geochemistry international, 2017)
For better understanding of the fluid phase sources of carbonatites of Guli alkaline-ultrabasic intrusion (Maymecha-Kotuy complex) we have studied isotope composition of He and Ne in the carbonatites of different formation stages. The data definitely point to the subcontinental lithospheric mantle (SCLM) as a primary source of fluid phase of Guli carbonatites. The absence of plume signature in such a plume-like object (from petrological point of view) could be explained in terms that Guli carbonatites have been formed at the waning stage of plume magmatic activity with an essential input of SCLM components.